Production of ¹⁵³Sm-labelled microparticles and dosimetric studies for potiental application in liver radioembolization / Nurul Hashikin Ab. Aziz - Nurul Hashikin, Ab. Aziz (2017)
Yttrium-90 (90Y)-microspheres have been increasingly used for transarterial radioembolization (TARE) of hepatocellular carcinoma (HCC). 90Y (a pure beta emitter) does not show sufficient post-procedural imaging capability. Samarium-153 (153Sm) may serve as a better alternative, due to its promising theranostic (therapy and diagnostic) characteristics. This thesis explored the production of 153Sm-microparticles and dosimetric studies for its application in TARE of HCC. A pilot study was performed to determine the suitable microparticle (diameter: 20-40µm) to be labelled with 153Sm. Two commercially available ion-exchange resins; Fractogel® EMD SO3 - and Amberlite® IR- 120H+ , each was labelled with 1g of samarium chloride ( 152SmCl3) in six different formulations and sent for neutron activation in the TRIGA PUSPATI research reactor. Radionuclide purity of these microparticles were tested via gamma spectrometry, and the optimum formulation for each microparticle was determined following a 48h radiolabelling efficiency study in distilled water and human blood plasma. Amberlite® IR-120H+ was chosen, as it possesses excellent (99.9%) radiolabelling efficiency and did not produced any radionuclide impurity following neutron activation. Physicochemical properties of the chosen microparticle before and after neutron activation was further investigated. Fourier transform infrared (FTIR) spectroscopy showed its unaffected functional group throughout the preparation processes. Energy dispersive x-ray (EDX) spectroscopy confirmed the absence of radionuclide impurity. The microparticles possess irregular surface with increased fragments (<10µm) following neutron activation, as seen via a field emission scanning electron microscope (FESEM). The measured particle density was 2.5g.cm-3 with specific radioactivity of 54Bq per microparticle, and settling velocity of 0.03cm.s-1 . Monte Carlo (MC) simulations were done using the Geometry and Tracking 4 (Geant4) software toolkit, to study the dosimetric accuracy of the routinely iv used Medical Internal Radiation Dose (MIRD) based partition model (PM) for TARE with 90Y-microspheres. It was found that PM markedly underestimated the normal liver dose by up to -78%, due to exclusion of cross-fire irradiation between the tumour and normal liver tissue. The model also overestimated both tumour and lung dose by up to 8 and 12%, respectively. These data can be used to recognise the cases with large dosimetric inaccuracy when PM is being used. Also, a corrected formula for lung dose was suggested for future used. Dosimetric assessment for TARE with 153Sm-microparticles was performed using similar MC method. Various treatment scenarios were simulated by targeting 120Gy to the tumour. The 153Sm-microparticles were able to deliver comparable tumour dose with normal liver and lung dose close to that of 90Y-microspheres, and other organ doses far below 1Gy. Finally, the simulations were repeated with other potential radionuclides; holmium-166 ( 166Ho), lutetium-177 (177Lu) and rhenium-188 (188Re), and the doses were compared with 90Y and 153Sm. 153Sm-microparticles showed great potential as alternative to 90Y with advantage of post-procedure imaging. It possesses ideal characteristics including; stable for neutron activation, excellent radiolabelling efficiency, absence of radionuclide impurities, stable in suspension, low production cost, and ability to deliver comparable tumour dose, without exceeding the organ dose limit. However, improvements should be made to its physical structure for better intraarterial delivery to the tumour.